COMMERCIAL BABY PORRIDGES IN NUTRITION OF INFANTS - I. N. Zakharova; T. E. Borovik; L. L. Stepurina; O. V. Osipenko; N. G. Zvonkova; Yu. A. Dmitrieva; T. V. Bushueva; E. B. Machneva ("Paediatrician" Publishers LLC, 2013)
The article covers the issue of the most important product among additional food for infants - baby porridges. It includes historical data on usage of various cereal crops in human nutrition. A special significance of porridges in culture of food and traditions of Russian population is highlighted. The authors give information about nutritional value and chemical composition of different cereals - buckwheat, rice, pearl-barley, millet, oats etc. A special attention is given to differences in concentrations of nutrients and micronutrients manufactured by different ways from the same kind of cereal. The necessity to feed infants with commercial baby porridges is based in the article. There are also represented characteristics of various commercial porridges for nutrition of infants: hypoallergenic, glutenfree and containing gluten, enriched with pre- and probiotics. The article also contains data on nutritional value of milk and milk-free porridges. The authors raised a discussion on possibility and standards of usage of different additional components, such as sugar, maltodextrin, honey, vanillin, vegetable oils in production of infant porridges. The selection of certain type of porridges as additional food for healthy and infants with different diseases and digestive disorders is based.